Child and adult thyroid monitoring after a reactor accident (CAThyMARA): Technical recommendations and remaining gaps. (September 2019) - Broggio, D.; Baudé, S.; Belchior, A.; Berkovskyy, V.; Bonchuck, Y.; Dewoghélaëre, J.; Etherington, G.; Fojtík, P.; Franck, D.; Gomez-Ros, J.M.; Gregoratto, D.; Helebrant, J.; et al.
Abstract: Following a severe nuclear reactor accident large amounts of radioactive iodine are released in the atmosphere. Health consequences estimation for the affected population is based on the dose assessment which can be derived from in vivo measurements. Since the uptake of radioactive iodine increases the thyroid cancer risk of children it is of particular interest to dispose of technical recommendations on thyroid monitoring, particularly for children. This paper summarizes recommendations that have been issued by a group of European radiation protection specialists during the CAThyMARA project. It covers technical aspects such as the choice of instruments, the calibration process, the measurement preparedness, the dose assessment and communication issues. This paper also discusses remaining gaps and serves as an introduction to other papers of this special issue. Highlights: Child and Adult Thyroid Monitoring After Reactor Accident. Introduces the outcomes of the CAThyMARA project. A summary of technical recommendations for emergency in vivo thyroid monitoring. Discusses remaining gaps.